Effect of the flavonoid baicalein as a feed additive on the growth performance, immunity, and antioxidant capacity of broiler chickens. (19th February 2019) - Zhou, Yefei; Mao, Shanguo; Zhou, Meixian
ABSTRACT: Baicalein, the main flavonoid extracted from the root of Scutellaria baicalensis Georgi, has been demonstrated to exert multiple pharmacological effects, and thus could be utilized as a potential feed additive in broiler chickens. This study evaluated the effects of broiler chicken diet supplementation with baicalein on growth performance, immunity, and antioxidant activity at levels of 100 and 200 mg/kg. No significant effect on average daily feed intake ( P > 0.05) of broilers with diets supplemented with baicalein was found compared to those on the basal diet or butylated hydroxytoluene (BHT ) during the 35-d feeding trial. The addition of baicalein to the basal diet significantly increased average body weight, body weight gain, average weight gain, and the feed conversion ratio of birds during 21 to 42 d and 7 to 42 d of age, respectively. The best numerical values for the overall growth performance were observed in broilers fed on diets containing 200 mg/kg of baicalein. Baicalein supplementation significantly increased the ratio of CD3 + /CD4 + and CD3 ± /CD8 +, the concentration of IFN-γ, anti-IB antibody titer, and the spleen index compared with the control group ( P < 0.05). Total cholesterol, the ratio of non-HDL-C/HDL-C, LDL-C/HDL-C, TC/HDL-C, triglycerides, and low-density lipoprotein cholesterol were significantly decreased after intake of baicalein compared with both the basal diet and the BHT-supplemented diet, whereas the SOD, GSH-Px, and CAT activity in the serum increased with the supplementation of baicalein. The T-AOC activity, T-SOD, and GSH-Px level in liver tissues was significantly increased by inclusion of baicalein, and intake of baicalein or BHT significantly decreased the malondialdehyde level found both in serum and meat tissue. Thus, the results obtained here indicate that the baicalein can be used as an effective natural feed additive in broiler chicken diets, and that 100 to 200 mg/kg can be considered as the optimum dosage.